2021
DOI: 10.1371/journal.ppat.1009816
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-mediated regulation of the arginine transporter of Toxoplasma gondii

Abstract: Intracellular parasites, such as the apicomplexan Toxoplasma gondii, are adept at scavenging nutrients from their host. However, there is little understanding of how parasites sense and respond to the changing nutrient environments they encounter during an infection. TgApiAT1, a member of the apicomplexan ApiAT family of amino acid transporters, is the major uptake route for the essential amino acid L-arginine (Arg) in T. gondii. Here, we show that the abundance of TgApiAT1, and hence the rate of uptake of Arg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 56 publications
(118 reference statements)
1
24
0
Order By: Relevance
“…The data in the present study indicate that Tg ApiAT6-1 functions as this alternative Arg transporter. We have recently shown that the expression of Tg ApiAT1 is up-regulated under Arg-limiting conditions and expressed at low levels under Arg-replete conditions [ 31 ]. The differential expression of Tg ApiAT1 may therefore allow these parasites to survive when Arg levels are limited, while Tg ApiAT6-1 may ensure regulated uptake of Arg and Lys under nutrient-rich conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The data in the present study indicate that Tg ApiAT6-1 functions as this alternative Arg transporter. We have recently shown that the expression of Tg ApiAT1 is up-regulated under Arg-limiting conditions and expressed at low levels under Arg-replete conditions [ 31 ]. The differential expression of Tg ApiAT1 may therefore allow these parasites to survive when Arg levels are limited, while Tg ApiAT6-1 may ensure regulated uptake of Arg and Lys under nutrient-rich conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, and on several other recent studies into Arg uptake in T . gondii [ 27 , 31 , 41 ], we can now propose a comprehensive model for the uptake of cationic amino acids into these parasites ( Fig 7 ). The scavenging of AA + by parasites results in a depletion of these amino acids in the host cell cytosol, causing upregulation of the host CAT1 AA + transporter [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations